2021
DOI: 10.33448/rsd-v10i16.23893
|View full text |Cite
|
Sign up to set email alerts
|

Bioecologia alimentar e reprodutiva como subsídio para o cultivo do peixe Centropomus undecimalis (Teleostei: Centropomidae) no Brasil: Uma Revisão Sistemática

Abstract: Diversos estudos têm sido realizados no Brasil com diferentes enfoques para as avaliações bioecológicas do Centropomus undecimalis (Bloch, 1792), peixe conhecido vulgarmente como robalo ou camurim. Estes estudos descrevem sobre a dinâmica populacional da espécie a partir de dados como peso, idade/crescimento, dieta alimentar e reprodução. Nesse contexto o objetivo do presente trabalho foi realizar uma revisão de literatura sobre a bioecologia alimentar e reprodutiva como subsídio para o cultivo do C. undecimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Martinelli (2010) also found similar data regarding the allometry of C. undecimalis in Ponta Negra, Natal, Rio Grande do Norte, and Gassman et al (2017) found similar data in their studies with this species in Venezuela. The positive allometry of females can be attributed to the availability of food resources in the study environment, to the fact that females need more energy for reproduction, to the food ecology strategies of the common snook described by Nascimento et al (2021) and Souza et al (2021) in the Tutóia region, state of Maranhão, as well as to the fact that the study area is inserted in the Parnaíba Delta Environmental Protection Area (EPA), a sustainable use conservation unit administered by The Brazilian Institute for the Environment and Renewable Natural Resources (IBAMA), created by a decree (no number) of 08/28/1996, at the request of environmentalists to protect the coastal ecosystem formed by mangroves and dunes located in the states of Maranhão and Piauí (Brasil, 2002;Silva, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinelli (2010) also found similar data regarding the allometry of C. undecimalis in Ponta Negra, Natal, Rio Grande do Norte, and Gassman et al (2017) found similar data in their studies with this species in Venezuela. The positive allometry of females can be attributed to the availability of food resources in the study environment, to the fact that females need more energy for reproduction, to the food ecology strategies of the common snook described by Nascimento et al (2021) and Souza et al (2021) in the Tutóia region, state of Maranhão, as well as to the fact that the study area is inserted in the Parnaíba Delta Environmental Protection Area (EPA), a sustainable use conservation unit administered by The Brazilian Institute for the Environment and Renewable Natural Resources (IBAMA), created by a decree (no number) of 08/28/1996, at the request of environmentalists to protect the coastal ecosystem formed by mangroves and dunes located in the states of Maranhão and Piauí (Brasil, 2002;Silva, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because it is a Sustainable Use Conservation Unit, it allows the extraction of its resources (ICMBio, 2017). In this context, studies on the reproductive biology of fish are important because they allow environmental managers to create standards so that fishing resources can be extracted in an orderly manner (Nascimento et al, 2021) avoiding the depletion of stocks.…”
Section: Introductionmentioning
confidence: 99%